2019
DOI: 10.1007/s13730-019-00431-2
|View full text |Cite
|
Sign up to set email alerts
|

A case of lupus vasculopathy presenting favorable renal outcome

Abstract: Noninflammatory necrotizing vasculopathy, also referred to as lupus vasculopathy, is not infrequently observed in the pathology of lupus nephritis. It affects vessels causing them to become severely narrowed and occluded by a mechanism involving immune complexes. We experienced a 51-year-old woman with lupus nephritis class IV + V, which was accompanied by lupus vasculopathy. Renal biopsy and light microscopy showed eosinophilic hyaline-like material in the afferent and/or efferent arterioles, which narrowed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…With respect to the first research question, we found that the proportion of severe arteriosclerosis was an independent predictor of clinical progression to ESRD for DKD patients. In lupus nephritis and IgA nephropathy, some studies have supported vascular lesions as independent risk factors for predicting renal disease progression [ 32 35 ]. Although the pathological classification of DKD included the vascular score in the original literature, the authors did not validate the relationship between vascular lesions and renal prognosis [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…With respect to the first research question, we found that the proportion of severe arteriosclerosis was an independent predictor of clinical progression to ESRD for DKD patients. In lupus nephritis and IgA nephropathy, some studies have supported vascular lesions as independent risk factors for predicting renal disease progression [ 32 35 ]. Although the pathological classification of DKD included the vascular score in the original literature, the authors did not validate the relationship between vascular lesions and renal prognosis [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…39 Eventually, immune complex deposits can cause blood vessel narrowing and occlusion, driving the lupus-related vasculopathy. 40 However, although blood vessels are so important in LE, the role of endothelial alteration in LE is far from being completely understood. Somehow, the immune system dysfunction contributes to vascular dysfunction in systemic LE, 41 which triggers most clinical manifestations of the disease.…”
Section: Discussionmentioning
confidence: 99%